Effect of Fermentation Time and Starbio Bioactivator Type and Local Microorganism (MOL) “Ginta” on The Nutritional Quality of Cassava Tuber Skin (Manihot Utilisima) - Bahria Nasution; Hasnudi; Nurzainah Ginting; Yunilas; Hamdan (Talenta Publisher, 2018)
BAHRIA NASUTION, 2018.